Ecto-5′-Nucleotidase (CD73) Inhibits Nociception by Hydrolyzing AMP to Adenosine in Nociceptive Circuits - Sowa, Nathaniel A. (Society for Neuroscience, 2010)
Ecto-5′-nucleotidase (NT5E, CD73) is a membrane-anchored protein that hydrolyzes extracellular adenosine 5′-monophosphate (AMP) to adenosine in diverse tissues but has not been directly studied in nociceptive neurons. We found that NT5E was located on peptidergic and nonpeptidergic nociceptive neurons in dorsal root ganglia (DRG) and on axon terminals in lamina II (the substantia gelatinosa) of spinal cord. NT5E was also located on epidermal keratinocytes, cells of the dermis, and on nociceptive axon terminals in the epidermis. Following nerve injury, NT5E protein and AMP histochemical staining were coordinately reduced in lamina II. In addition, AMP hydrolytic activity was reduced in DRG neurons and spinal cord of Nt5e(−/−) mice. The antinociceptive effects of AMP, when combined with the adenosine kinase inhibitor 5-iodotubericidin, were reduced by ∼50% in Nt5e(−/−) mice and were eliminated in Adenosine A(1) receptor (A(1)R, Adora1) knock-out mice. Additionally, Nt5e(−/−) mice displayed enhanced sensitivity in the tail immersion assay, in the complete Freund's adjuvant model of inflammatory pain and in the spared nerve injury model of neuropathic pain. Collectively, our data indicate that the ectonucleotidase NT5E regulates nociception by hydrolyzing AMP to adenosine in nociceptive circuits and represents a new molecular target for the treatment of chronic pain. Moreover, our data suggest NT5E is well localized to regulate nucleotide signaling between skin cells and sensory axons.